Use of Epiphysiodesis as Treatment for a Proximal Physeal Tibial Fracture in a Dog - Picavet, Pierre P.; Bouvy, Bernard; Hamon, Martin; Lefebvre, Michael; Balligand, Marc (VCOT Open, 2019)
Objective The aim of this study was to describe the use of epiphysiodesis by the means of a screw to treat a proximal tibial Salter–Harris II fracture associated with a tibial tuberosity avulsion in a 4.5-month-old Airedale Terrier.Study design A healing proximal tibial epiphyseal fracture was observed after a 10-day period. Tibial plateau angle was 40°. The fracture was treated by the insertion of a fluoroscopy-guided 3.5-mm cancellous screw.Results Successful healing of fractures and levelling of tibia plateau were obtained. Final tibial plateau angle was 8°. At long-term follow-up (18 months), owners reported sustained and full functional recovery.Conclusion Prior to ossification of the proximal tibial physis, epiphysiodesis with a screw can be used as a treatment of sub-acute, moderately displaced, Salter–Harris I or II fractures.
Keywords: tibial plateau slope; epiphysiodesis; growing dogs; Salter–Harris II fracture